How do I show that $$\lim_{x \to x_0} \frac{x^{\alpha }-x_{0}^{\alpha } }{x-x_0} = \lim_{x \to 1} \frac{x_{0}^{\alpha }x^{\alpha }-x_{0}^{\alpha } }{x_0 x-x_0}$$


For $x_0\neq 0$, let $x=yx_0$ with $y\to 1$

$$\lim_{x \to x_0} \frac{x^{\alpha }-x_{0}^{\alpha } }{x-x_0} = \lim_{y \to 1} \frac{(yx_0)^{\alpha }-x_{0}^{\alpha } }{(yx_0)-x_0} =\lim_{y \to 1} \frac{x_{0}^{\alpha }y^{\alpha }-x_{0}^{\alpha } }{x_0 y-x_0}$$

For $x_0=0$

$$\lim_{x \to x_0} \frac{x^{\alpha }-x_{0}^{\alpha } }{x-x_0} =\lim_{x \to 0} x^{\alpha-1 }$$

  • $\begingroup$ In the case $x_0 = 0$ your starting equation $x = yx_0$ does not define $y$. You should at least point out that the case $x_0 = 0$ must be treated separately. $\endgroup$ – Gibbs Apr 14 '18 at 9:50
  • $\begingroup$ @Gibbs yes of course the case $x_0=0$ should be treated a part $\endgroup$ – gimusi Apr 14 '18 at 9:54

Just define $y = \frac{x}{x_0}$ and observe that when $x$ goes to $x_0$, $y$ goes to 1. Then you can rewrite $$\lim_{x \rightarrow x_0} \frac{x^a-x_0^a}{x-x_0} = \lim_{y\rightarrow 1} \frac{y^ax_0^a-x_0}{yx_0-x_0}. $$ I divided by $x_0$, so treat the case $x_0 = 0$ separately.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.